2021
DOI: 10.14693/jdi.v28i2.1251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Sella Turcica Bridging and Dental Anomalies

Abstract: Objectives: This study aims to evaluate the relationship between the morphological variations of Sella Turcica (ST) and dental anomalies. Methods: This study included 765 individuals between the ages of 13 and 35. ST morphology was examined in 3 groups as no calcification, partially calcified and completely calcified according to the interclinoid ligament (ICL) on lateral cephalometric films, and it was examined and evaluated in terms of its relationship to impacted canines (unilateral and bilateral), impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Research has recently looked into the link between dentoskeletal anomalies and craniofacial and cervicovertebral anomalies [ 18 , 22 26 ]. Consistent with the descriptive results of our study, several studies have reported that the prevalence of incomplete STB was higher than the complete form [ 19 , 22 , 27 to 29 ]. On the other hand, other studies have found that the incomplete form of PP was more prevalent than the complete type [ 22 and 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Research has recently looked into the link between dentoskeletal anomalies and craniofacial and cervicovertebral anomalies [ 18 , 22 26 ]. Consistent with the descriptive results of our study, several studies have reported that the prevalence of incomplete STB was higher than the complete form [ 19 , 22 , 27 to 29 ]. On the other hand, other studies have found that the incomplete form of PP was more prevalent than the complete type [ 22 and 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…e dimensions of sella turcica were also strongly related to the subjects' age [34,41]. However, contrary to those findings, some research found no link between age and STB or PP [4,27].…”
Section: Stb and Pp Age And Gendermentioning
confidence: 76%
“…However, no other significant correlations were found. Consistent with the present results, Jankowski et al [21], Kaya et al [37], Karaman et al [38], and Jankowski et al [39] demonstrated a significant correlation between dental anomalies and ST bridge. Alam and Alfawzan [40] indicated a higher frequency of ST bridge in patients with cleft.…”
Section: Discussionsupporting
confidence: 92%